Communication Skills of Autistic Children at the Karya Tulus Special School in Medan City for Social Interaction - Rizky Chairunnisyah; Sori Monang (Budapest International Research and Critics University, 2023)
The birth of a child in family life is a real source of happiness for a married couple. The best hope is directed at the growth and development of children. However, there are several births of children that are not the family's expectations. Children with neurological disorders (neurodevelopmental disorders). Autism is one of the children who have a neurological disorder which is directed at sensory integration disorders. Where this results in a lack of nerve function, one of which is in communicating. This study aims to determine the communication skills of autistic children in social interaction at Special Schools (SLB)-C Karya Tulus, Medan City. The method used is a type of qualitative research method with the